Tantangan Dan Peluang Implementasi Good Corporate Goverance Di Usaha Kuliner Dapur Bestie: Perspektif Stakeholder - Yoka Yanarid; Masiyah Kholmi (Jurnal Pemimpin Bisnis Inovatif, 2024)
This research aims to explore the challenges and opportunities of implementing Good Corporate Governance (GCG) in Dapur Bestie, a culinary business, from the stakeholders' perspective. Through a combination of surveys, interviews, and document analysis, we gained insights into the factors influencing the company's GCG practices. The findings indicate that Dapur Bestie faces challenges such as stringent regulations, resource constraints, supply chain complexity, and resistance to change. However, there are significant opportunities to strengthen GCG practices, including enhancing brand reputation, operational efficiency, and stakeholder engagement. The integrity of GCG practices within the organizational culture is identified as key to long-term success. This research suggests strategic steps that Dapur Bestie can take to reinforce their GCG practices, considering the company's vision and the expectations of all involved parties. It is hoped that sustained efforts to improve GCG will yield long-term benefits for the company and society at large.